Effectiveness of Pre-operative Rectal Misoprostol in Reducing Blood Loss during Cesarean Section for Placenta Previa and Manual Removal of Retained Placenta: A Parallel Placebo-Controlled Study - Akpan, Ubong; Asibong, Udeme; Arogundade, Kazeem; Akpanika, Chinyere; Ekot, Mabel; Etuk, Saturday (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Primary postpartum hemorrhage (PPH) contributes significantly to the high maternal mortality ratio, especially in the low resource nations. Placenta previa and retained placenta are major causes of postpartum hemorrhage. Uterotonics like misoprostol are medication used to improve uterine contractility with the purpose of reducing uterine bleeding after delivery of baby. Most studies on misoprostol for the prevention of obstetric hemorrhage have been focusing on its postpartum use. AIM: The aim of this study was to assess the effectiveness of pre-operative misoprostol in reducing blood loss during cesarean section for placental previa and manual removal of retained placenta. METHODS: This was a placebo-controlled study involving 154 women who were randomly assigned to the treatment and control groups. The study group received 400 ug of misoprostol rectally just before the commencement of the procedure. Estimation of blood loss was done in a standardized way. Data were analyzed using SPSS version 23. The level of significance was set at p < 0.05. RESULTS: The average age of the participants was 31.64 years. The overall incidence of PPH was comparable in both groups (0.070), however, misoprostol group experienced lower incidence of severe PPH compared to the placebo (p = 0.013). Other maternal and perinatal outcomes were comparable. CONCLUSION: Excessive intraoperative and immediate post-operative bleeding can be prevented with pre-operative misoprostol. It should be made available for high-risk obstetrics procedures.